Lifetime determination via the particle-γ coincidence Doppler-shift attenuation method. (December 2020) - Prill, S; Bohn, A; Everwyn, V; Färber, M; Hennig, A; Kluwig, F; Petkov, P; Scholz, P; Spieker, M; Weinert, M; Wilhelmy, J; Zilges, A
Abstract: This paper illustrates the principle of the Doppler-shift attenuation method (DSAM) using particle-γ coincidences, a method for determining lifetimes of excited nuclear levels in the range of few femtoseconds up to one picosecond. The coincident detection holds several advantages towards conventional DSAM experiments, such as the elimination of background and feeding transitions. Using the experimental data on 94 Zr, the concept of the (p, p'γ) DSAM analysis is presented. Additional experimental results are highlighted.